PENGARUH KEPERCAYAAN, KEBIASAAN MENGGUNAKAN PRODUK TERHADAP KEPUASAN KONSUMEN SERTA LOYALITAS KONSUMEN DALAM MEMBELI MEREK SAMSUNG DI TOKO “Y” - Endang Kurniawati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2019)
The purpose of this study was to analyze the influence of trust, the habit of using products to customer satisfaction and consumer loyalty in buying the Samsung brand in the "Y" store. The population used is the entire consumer who is a customer of the "Y" store with a purchase of at least 1 (one) time and the amount is unknown. Given the number of population is not known with certainty the number, so the basis for determining the sample determined sample is determined by a formula so that the number of samples is 50 respondents.Based on testing shows that the influence of trust on customer satisfaction is significant, meaning that the higher the level of consumer confidence in a product, the more it will increase customer satisfaction. The influence of the habit of using products on customer satisfaction is significant, meaning that if the habits of consumers in using the product increases. Consumer satisfaction can be an intervening variable between the habit of using products to consumer loyalty. The effect of consumer satisfaction on consumer loyalty is significant, meaning that if customer satisfaction increases, consumer loyalty will increase.